2005
DOI: 10.1159/000087448
|View full text |Cite
|
Sign up to set email alerts
|

The Aging, Demographics, and Memory Study: Study Design and Methods

Abstract: Objective: We describe the design and methods of the Aging, Demographics, and Memory Study (ADAMS), a new national study that will provide data on the antecedents, prevalence, outcomes, and costs of dementia and ‘cognitive impairment, not demented’ (CIND) using a unique study design based on the nationally representative Health and Retirement Study (HRS). We also illustrate potential uses of the ADAMS data and provide information to interested researchers on obtaining ADAMS and HRS data. Methods: The ADAMS is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
398
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 339 publications
(409 citation statements)
references
References 47 publications
0
398
1
Order By: Relevance
“…Composite scores for ADL difficulty were computed and cut-offs determined a priori to represent no limitations (0), mild/moderate limitations (1-2), and severe limitations (3 or more). The HRS tests cognitive function using well-described methods; [29][30][31][32][33] final models used a binary measure to describe patients as having no cognitive impairment versus any cognitive impairment. Two binary measures related to disability were obtained from the HRS data: whether the patient required nursing home services during the most recent HRS interview, or had used home health care services in the 2 years prior to the interview.…”
Section: Data Sources and Measures Of Disability And Social Determinamentioning
confidence: 99%
“…Composite scores for ADL difficulty were computed and cut-offs determined a priori to represent no limitations (0), mild/moderate limitations (1-2), and severe limitations (3 or more). The HRS tests cognitive function using well-described methods; [29][30][31][32][33] final models used a binary measure to describe patients as having no cognitive impairment versus any cognitive impairment. Two binary measures related to disability were obtained from the HRS data: whether the patient required nursing home services during the most recent HRS interview, or had used home health care services in the 2 years prior to the interview.…”
Section: Data Sources and Measures Of Disability And Social Determinamentioning
confidence: 99%
“…38 The validity of these categories is supported by the clear trends in functional limitations with which they are associated. We assessed the mean number of limitations in instrumental activities of daily living (IADLs; preparing meals, grocery shopping, making phone calls, taking medications, managing money) and found that those in the normal, mild CI, and moderate / severe CI categories had an average of 0.4, 1.1, and 2.5 IADL limitations, respectively (P<.001).…”
Section: Measurement Of Cognitive Function and Cognitive Category Defmentioning
confidence: 99%
“…The neuropsychological battery used in the study has been described in previous work from our group (Breitner et al, 1995) and has been adopted by a growing number of cohort and casecontrol studies of aging and dementia (Steffens et al, 2004;Langa et al, 2005;van der Walt et al, 2005;Plassman et al, 2006;Tschanz et al, 2000Tschanz et al, , 2002Tschanz et al, 2006). A brief description of the measures and the order of test administration follow:…”
Section: Neuropsychological Measuresmentioning
confidence: 99%